Widespread influence of artificial light at night on ecosystem metabolism - Johnston, Alice S. A.; Kim, Jiyoung; Harris, Jim A. (Springer, 2025)
Artificial light pollution is increasing worldwide with pervasive effects on ecosystem structure and function, yet its influence on ecosystem metabolism remains largely unknown. Here we combine artificial light at night (ALAN) intensity metrics with eddy covariance observations across 86 sites in North America and Europe to show that ALAN indirectly decreases annual net ecosystem exchange by enhancing ecosystem respiration (Re). At half-hourly and daily scales, we detect consistent nonlinear interactions between ALAN and night duration, with Re increasing under higher ALAN and partially decoupling from gross primary production. At the annual scale, gross primary production shows no direct ALAN response and is instead influenced by the growing season length and urban proximity, whereas Re responds more strongly and consistently across timescales. Our findings show that ALAN disrupts the fundamental energetic constraints on ecosystem metabolism, warranting the inclusion of light pollution in global change and carbon–climate feedback assessments.
The FLUXNET2015 data analysed in this study are available at https://fluxnet.fluxdata.org/data/fluxnet2015-dataset/ (ref. 55) and are subject to the FLUXNET data policy (https://fluxnet.org/data/data-policy). As the redistribution of raw half-hourly flux data is not permitted, we provide only derived products, including daily and annual summaries, processed variables and model outputs, which are available under a CC-BY 4.0 license via Figshare at https://doi.org/10.6084/m9.figshare.29958455 (ref. 58). The ALAN metrics used here are available at https://doi.org/10.3390/rs9060637 (ref. 32). The R code used for data processing and analysis in this study is available via Figshare at https://doi.org/10.6084/m9.figshare.29958455 (ref. 58).
Keywords: 4101 Climate Change Impacts and Adaptation; 31 Biological Sciences; 3103 Ecology; 41 Environmental Sciences